2014
DOI: 10.1002/ajpa.22532
|View full text |Cite
|
Sign up to set email alerts
|

Brief communication: The size of the human frontal sinuses in adults presenting complete persistence of the metopic suture

Abstract: The notion of absence of the frontal sinuses in human individuals presenting a persistence of the metopic suture is considered as classical in many treatises of reference; however, precise studies are very rare and even controversial. The purpose of this study was thus to provide original data to confirm or refute this classical affirmation with the perspective of some original insights into biological significance of the frontal sinuses and the factors influencing their exceptional polymorphism. The material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 43 publications
(111 reference statements)
11
62
0
Order By: Relevance
“…We arbitrarily named these classes "small", "medium-sized" and "large". In our sample, the most common type was "medium-sized", followed by "large" and then "small", which is in line with the literature (Guerram et al, 2014;Y€ uksel Aslier et al, 2016). "Small" sinuses seem to be distinguished by no pneumatization or pneumatization of only the medial part of the orbital roof, with all dimensions smaller than in the other two types; "mediumsized" sinuses seem to be distinguished by pneumatization of the medial and a portion of the central part of the orbital roof with all dimensions (on average) between the values for "small" and "large" sinuses; while "large" sinuses seem to be distinguished by predominant pneumatization of the orbital roof (and by the largest of all sinus dimensions).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We arbitrarily named these classes "small", "medium-sized" and "large". In our sample, the most common type was "medium-sized", followed by "large" and then "small", which is in line with the literature (Guerram et al, 2014;Y€ uksel Aslier et al, 2016). "Small" sinuses seem to be distinguished by no pneumatization or pneumatization of only the medial part of the orbital roof, with all dimensions smaller than in the other two types; "mediumsized" sinuses seem to be distinguished by pneumatization of the medial and a portion of the central part of the orbital roof with all dimensions (on average) between the values for "small" and "large" sinuses; while "large" sinuses seem to be distinguished by predominant pneumatization of the orbital roof (and by the largest of all sinus dimensions).…”
Section: Discussionsupporting
confidence: 91%
“…Third, the present data strongly suggest a simple and straightforward sinus classification with practical implications. There is no generally accepted classification of frontal sinuses, but some authors have used descriptive categories such as “aplasia”, “hypoplasia”, “medium size” and “hyperplasia” (Guerram et al, ; Yüksel Aslier et al, ). In Guerrram's study the most prevalent were medium sinuses (76.2%), followed by sinus hyperplasia (11.9%), hypoplasia (9.4) and aplasia (2.5%) (Guerram et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This trait is relatively frequent in human populations; probably caused by increased osteolytic activity during bone resorption; as a result, the sinus extends antero‐posteriorly either toward the outer diploë of frontal bone, toward the inner plate, or toward lateral structures (Fatu et al, ). It has been found in 2–10% of humans from different geographic populations (Akhlaghi et al, ; Fatu et al, ; Flanigan et al, ; Guerram et al, ; Park et al, ), in 23.7% of Melanesians (Vinyard & Smith, ) and in more than 25% of Inuits (Hanson & Owsley, ). In disagreement with other studies reporting a high frequency of FS aplasia in different populations (Akhlaghi et al, ; Fatu et al, ; Flanigan et al, ; Hanson & Owsley, ; Park et al, ; Vinyard & Smith, ), it was not found in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…The human frontal bones begin to ossify in the mesenchyme via two ossification centers at approximately eight weeks gestation which appears near frontal tuber. At birth the two halves of frontal bone remain separate by the metopic suture which is replaced by bone at about 2 years .The term metopic is from Greek meaning "in the middle 3,4 of the face".…”
Section: Introductionmentioning
confidence: 99%